THE INFLUENCE OF THE NUMBER OF TOURIST VISITS, AVERAGE LENGTH OF TOURIST STAY AND THE NUMBER OF RESTAURANTS/EATING HOUSES ON THE REGIONAL INCOME OF WEST MANGGARAI DISTRICT - Isabella Laura Batistuta Jehau; Anak Agung Bagus Putu Widanta (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Since the establishment of the Komodo National Park as one of the new Seven Wonders of the Natural World, NTT has become the entry point for Indonesian tourism apart from Bali, which is already very well known. The local government in West Manggarai Regency has adopted a policy to carry out development in the tourism sector which is expected to make a sufficient contribution to regional development. The aim of this research is to further examine the influence of the number of tourist visits, the average length of stay of tourists, and the number of restaurants/restaurants, on Regional Original Income (PAD) in West Manggarai Regency. This research design uses an associative quantitative approach. The research location is West Manggarai Regency, Flores, NTT. This research uses regression data. The number of observations in this research is 8 years in the 2015–2022 time period multiplied by quarters so = 32 observations. The results of this research found that the number of tourist visits, the average length of stay of tourists, and the number of restaurants/restaurants simultaneously influence regional original income. The number of tourist visits partially has a positive and significant effect on local income (PAD), the average length of stay of tourists partially has a negative and insignificant effect on local income, the number of restaurants/restaurants has a positive but not significant effect on local income ( PAD).